The development of multimedia prototype courseware for primary school students: investigate the earth and the universe (constructivism approach) / Azizul Akmal Mohamad Mazuki - Mohamad Mazuki, Azizul Akmal (2007)
The objective of this research is to develop a multimedia prototype courseware for children below 12 years old. The science topic of Investigating the Earth and the Universe is the main domain of this research. In this research, the constructivism learning theory is used as the research method, while the ADDIE model is used to develop the multimedia prototype courseware. The development of this courseware is conducted by using various software such as Macromedia Flash MX, Adobe Photoshop, Adobe Illustrator and Sound Force to create a good production of a courseware. This prototype usability testing has been tested to about'30 respondents from students of standard 6 at Sekolah Kebangsaan Jalan Kebun, Klang. As the result, it has shown that the courseware is easy to use, it can increase student's interest in aerospace subjects and could provide more science knowledge compare the traditional way of learning. Computer animations and simulations are also being used to help student to understand the important information of this topics. It is hope that, that this prototype could be used by students and teachers as the teaching and learning material support.